2018
DOI: 10.1097/ccm.0000000000003069
|View full text |Cite
|
Sign up to set email alerts
|

Climate of Respect Evaluation in ICUs: Development of an Instrument (ICU-CORE)

Abstract: We created a reliable set of scales to measure the climate of respectfulness in intensive care settings. These measures can be used for ongoing quality improvement that aim to enhance the experience of ICU patients and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…This study has confirmed the validity and reliability of the Persian version of the IDCQ in assessing dignity‐based care among Iranian nurses. The CVI and CVR values, which were determined to be 0.98 and 0.78, respectively, align with the results of previous studies (Beach et al., 2018 ; Zamanzadeh et al., 2015 ). The KMO value of 0.898 indicates the data's suitability for factor analysis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study has confirmed the validity and reliability of the Persian version of the IDCQ in assessing dignity‐based care among Iranian nurses. The CVI and CVR values, which were determined to be 0.98 and 0.78, respectively, align with the results of previous studies (Beach et al., 2018 ; Zamanzadeh et al., 2015 ). The KMO value of 0.898 indicates the data's suitability for factor analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Standardized instruments, such as the Climate of Respect Evaluation–Intensive Care Unit (CORE‐ICU), Direct Observation Checklist (DOC) and ICU Dignified Care Questionnaire (IDCQ), are essential for evaluating how nurses uphold patient dignity in intensive care units (Beach et al., 2018 ; Carrese et al., 2017 ; Liang et al., 2022 ). While the CORE‐ICU instrument captures the clinical staff's perspectives on ICU treatment, it does not specifically address the distinct role of nurses (Beach et al., 2018 ). The DOC, a checklist‐based instrument, has limitations, including the requirement for a professional evaluator and the possibility of varied responses due to evaluator differences and behavioural changes (Carrese et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing on Leape’s insights about the importance of respectful culture, 11 we can ask clinicians to report on the culture of respect in their workplace. 14 While it may be difficult to prove that any specific instance of disrespect or microaggression is indeed intended, we do not need to judge each instance if we can routinely measure and find patterns.…”
Section: Epistemic Injustice In Health Systemsmentioning
confidence: 99%
“…The EDMCQ helps advance the field by providing ways to measure ethical decision-making climate, thus facilitating future descriptive and intervention studies focusing on institutional and ethical culture to improve patient and family outcomes. Another benefit of the EDMCQ and other instruments that focus on the more humanistic aspects of medicine 57 is that it draws attention to an institutional prioritization of ethics and ethical climate amongst clinicians and administrators. 58 The EDMCQ is an important step in improving the ethical decision-making climate of ICUs around intensity of end-of-life care and understanding its subsequent impact on the patient and family experience.…”
mentioning
confidence: 99%